The Emergence of AI and ChatGPT: Implication for Religion Sustainability in Africa - Oyasor, Emmanuel Imuede (International Journal of Social Science and Religion (IJSSR), 2024)
The swift development of artificial intelligence (AI) technology, including the conversational AI tools like ChatGPT, has had a profound impact on several industries, including business, education, and communication. ChatGPT provides creative ways to preserve holy writings, teach religion, and make spiritual counselling more accessible. It also has special religious ramifications, especially in Africa where religion is closely linked to social identity and unity. This study examines how AI and religion sustainability connect in Africa, stressing both the advantages and disadvantages of using AI into religious rituals. These tools encourage inclusivity and involvement, particularly among younger generations. Their adoption, however, presents moral questions, such as the possibility of misinterpreting religious doctrine, the commercialization of spirituality, and challenges to established religious authority. This study critically investigates how AI shapes worldviews and religious experiences, drawing on theoretical stances such social cognitive theory. It makes the case for a well-rounded strategy that preserves the holiness and integrity of religious traditions while embracing the advantages of AI. The study adds to the continuing conversation on maintaining religious significance in a time of rapid technology advancement by highlighting culturally appropriate implementations and cooperative efforts among engineers, religious leaders, and legislators.